PSYCHOLOGICAL DYNAMICS AND COPING MECHANISMS OF WOMEN INVOLVED IN ISLAMIC POLYGAMOUS MARRIAGES: Received: 28th February 2024 Revised: 09t April 2024, 16th April 2024, 30th April 2024 Accepted: 05th March 2024 - Gintarė Sereikaitė-Motiejūnė (LIFE: International Journal of Health and Life-Sciences, 2024)
This study explores the coping mechanisms and religious beliefs employed by women in polygamous relationships to manage emotional distress, and the extent to which this approach challenges or reinforces patriarchal structures within these relationships. Data collected a closed Facebook group for Muslim women only reveal that women in polygamous relationships often experience psychological and emotional distress. To cope, they commonly resort to religious faith, acceptance of fate, and compromise with co-wives. While these strategies help manage emotional distress, they can potentially reinforce patriarchal structures within these relationships. The research provides a nuanced perspective, arguing that these coping mechanisms can be seen both as a form of resistance against and an acceptance of patriarchal norms. The study also underscores the need for further research into factors such as stress levels, coping skills, and marital factors that can impact behavioral, emotional, and cognitive outcomes in polygamous marriages. To conclude, in polygamous relationships, women often use avoidance and religious justification as coping mechanisms. While these strategies provide temporary relief or spiritual comfort, they don't address the long-term psychological harm or inherent gender inequalities.